More stars stay, but the brightest ones still leave: Job hopping in the shadow of patent enforcement - Ganco, Martin; Ziedonis, Rosemarie H.; Agarwal, Rajshree (Strategic Management Journal, 2015)
Competitive advantage often rests on the skills and expertise of individuals who may leave for rival organizations. Although institutional factors like non‐compete regimes shape intra‐industry mobility patterns, far less is known about firm‐specific reputations built through patent enforcement. This study formally models and empirically tests how a firm's prior litigiousness over patents (i.e., its reputation for IP toughness) influences employee mobility. Based on inventor data from the U.S . semiconductor industry, we find that litigiousness not only diminishes the proclivity of inventive workers to “job hop” to others in the industry, it also shifts the distribution of talent released to the market. The study contributes new insights linking firm‐level reputations as tough legal enforcers to the “stay versus exit” calculus of knowledge workers . Copyright © 2014 John Wiley & Sons, Ltd.